Using Mathematical Modelling to Evaluate Human Papillomavirus Vaccination Programs in Canada - Rogers, Carley (Université d'Ottawa / University of Ottawa, 2013)
Mathematical models provide unique insights to real-world problems. Within the context of infectious diseases, models are used to explore the dynamics of infections and control mechanisms. Human papillomavirus (HPV) globally infects about 630 million people, many of these infections develop into cancers and genital warts. Vaccines are available to protect against the most prevalent and devastating strains of HPV. The introduction of this vaccine as part of a national immunization program in Canada is a complex decision for policy-makers in which mathematical models can play a key role. We use the current recommendations provided by the World Health Organization to explore the integral role mathematical models have in the decision to incorporate the HPV vaccine within a national immunization program. We then provide a review of the literature discussing the role of mathematical models in the decision to include a vaccine in a national immunization program within the context of the HPV vaccine. Next, we evaluate the current standing of mathematical models used within the context of HPV immunization, to highlight the types of models used, underlying assumptions and general recommendations made about these immunization programs. Then, we create and analyze a model to explore the possibility of bettering the current HPV vaccine strategy in Canada. We focus on the effects of the grade of vaccination and the number of doses required to eradicate the targeted strains of HPV.
Keywords: Mathematical Model; ODEs; Human Papillomavirus; HPV; vaccine; Canada; Ordinary Differential Equations; Dosing Schedule; Grade of Vaccination; Dose; National Immunization Program; Literature Review